PROBLEM-SOLVING AND PROBLEM-POSING LEARNING MODEL ENRICHED WITH THE MULTIPLE REPRESENTATION IN TETRAHEDRAL CHEMISTRY TO ENHANCE STUDENTS’ CONCEPTUAL UNDERSTANDING - Nurma Yunita Indriyanti; Sulistyo Saputro; Rizki Lukman Sungkar (EDUSAINS, 2020)
MODEL PROBLEM SOLVING DAN MODEL PROBLEM POSING DILENGKAPI MULTI REPRESENTASI TETRAHEDRAL KIMIA DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA AbstractA learning model has its characteristics with advantages and disadvantages. A Teacher has a particular way of delivering chemistry materials. This study aims to investigate the implementation of Thinking Aloud Pair Problem Solving (TAPPS) and Problem Posing (PP) to enhance students' conceptual understanding of the topic of the mole concept. The learning model implemented was enriched with the tetrahedral chemistry representation, which included levels of the human element, macroscopic, sub-microscopic, and symbolic. This research used a quasi-experimental method with a randomized pretest-posttest comparison group research design. Data collection used paper-and-pencil tests to sixty-four grade 10 students in a public high school in Sragen, Indonesia. Data analysis employed an independent sample t-test. The research findings indicated that the PP model was able to generate a higher degree of students' conceptual understanding than the TAPPS model and have more students with sound conceptual understanding than the TAPPS model. The chemistry teaching integrated with the tetrahedral chemistry representation increased students' sub-microscopic and symbolic levels of understanding. The new approach should be embedded in every chemistry learning model for enhancing students' understanding.AbstrakSebuah model pembelajaran mempunyai ciri tersendiri dengan kelebihan dan kekurangannya. Guru mempunyai cara khusus dalam menyampaikan materi kimia. Penelitian ini bertujuan untuk menyelidiki penerapan Thinking Aloud Pair Problem Solving (TAPPS) dan Problem Posing (PP) untuk meningkatkan tingkat pemahaman konseptual siswa dalam materi konsep mol. Model pembelajaran yang diterapkan tersebut diperkaya dengan representasi tetrahedral kimia, yang mencakup level human element, makroskopis, submikroskopis, dan simbolik. Penelitian ini menggunakan metode eksperimen semu dengan desain penelitian komparasi grup pretest-posttest yang diacak. Pengumpulan data menggunakan tes tertulis terhadap 64 siswa kelas 10 dari salah satu SMA di Sragen, Indonesia.  Analisis data menggunakan independent sample t-test. Hasil penelitian ini mengindikasikan bahwa model PP mampu menghasilkan tingkat pemahaman konseptual siswa yang lebih tinggi daripada model TAPPS. Pembelajaran kimia yang terintegrasi dengan representasi tetrahedral kimia mampu meningkatkan tingkat pemahaman sub-mikroskopis dan simbolis siswa. Pendekatan baru tersebut perlu dimasukkan di setiap model pembelajaran kimia untuk meningkatkan pemahaman siswa.